Impact of the COVID-19 Pandemic on STIs and HIV Services in Sleman District, Yogyakarta, Indonesia - Pudjiati, Satiti Retno; Rusetiyanti, Nurwestu; Susetiati, Devi Artami; Alfieri, Alessandro (Journal of Pakistan Association of Dermatologists, 2022)
Background Sexually transmitted infections (STIs) are currently the highest risk factor for transmitting HIV infection. The incidence of HIV and STIs increases every year and there are still many obstacles for People Living with HIV/AIDS (PLWHA) to get access to care and treatment. Since the WHO declared the COVID-19 pandemic and the implementation of regional quarantine and social distancing, the mobilization of people who should receive health services, including people with HIV and STIs, has decreased. These circumstances can neither achieve the Getting to Zeros program nor the triple elimination program. Currently, there are no reports on the impact of the COVID-19 pandemic on services and coverage of STIs and HIV in Indonesia. This study aimed to determine the impact, especially in Sleman Regency, Yogyakarta. Methods This epidemiological survey was conducted with a retrospective design and used secondary data. Restrictions on community mobility were implemented to prevent the spread of COVID-19 starting in April 2020. Data were collected from three hospitals and three primary health care (PHCs) in Sleman Regency, Yogyakarta, Indonesia, with STIs and HIV services, namely Dr. Sardjito Hospital, UGM Academic Hospital, Yogyakarta, Sleman Regional General Hospital, Tempel 1 Primary Health Care, Depok 3 Primary Health Care, and Mlati 1 Primary Health Care. Data came from the registry at the research sites. The data obtained were tabulated and presented in the form of a table and analyzed descriptively. Results There was a decrease in patient visits to STIs and HIV services before and during the COVID-19 pandemic, by 34.48% and 0.23%, respectively. For laboratory examinations related to the diagnosis of STIs, there were variations in changes, whereby gonorrhea examinations decreased by 49.77%, examinations for detecting genital warts increased by 42.86%, VDRL examinations decreased by 40.22%, TPHA examinations decreased by 22.54%, and HIV tests decreased by 4.12% in the period during the COVID-19 pandemic. For the number of visits by patients taking ARVs, there was an increase of 11.6% during the COVID-19 pandemic compared to before the COVID-19 pandemic. In laboratory examinations related to the triple elimination program in pregnant women, there were changes, namely in hepatitis B examination, there was an increase of 4.72%, HIV examination, a decrease of 1.54%, and syphilis examination, there was a decrease of 1.15%. Conclusion The COVID-19 pandemic has impacted some services related to STIs and HIV. Further research on a broader scale is needed to confirm the extent of the impact. Strategies to improve the examination and management of STIs and HIV cases must always be prepared and their effectiveness evaluated in their implementation during this pandemic or in the event of other disease outbreaks in the future. Keywords: COVID-19 pandemic, HIV, STIs